Young Lives School Survey, 2016-17: Value-added Analysis in India - Rolleston, C; Moore, R (Young Lives, 2018)
Student outcomes are often used as indicators of the ‘quality’ or ‘effectiveness’ of schools and teachers, and indeed as indicators of the quality of education systems more broadly. Student test scores, in combination with relevant contextual data, provide policymakers and educational researchers with a certain amount of information on what is happening in schools or classes where students are performing more or less well, at least in terms of ‘levels’ of performance. However, they are limited because non-school factors play an important role in determining levels of performance, and also because such cross-sectional data do not provide information on how much progress has been made. Measures of school ‘value-added’ attempt to address some of the difficulties in assessing school quality based on levels of performance alone. These measures are based on student progress, and aim to isolate and measure the contribution which schools make to improving student learning outcomes. This report uses a value-added framework to examine school effectiveness in Andhra Pradesh and Telangana, using data from the Young Lives 2016-17 school survey.